PANTI SOSIAL ANAK PROVINSI KALIMANTAN BARAT - Nurul Izzah Aulia; Affrilyno Affrilyno; Bontor Jumaylinda BR Gultom (JMARS: Jurnal Mosaik Arsitektur, 2023)
Law of the Republic of Indonesia No. 35 of 2014 confirms that children have the right to survival, growth and development and to receive protection from all acts of crime, violence, exploitation and neglect. Even though government regulations have been enacted, there are still cases of crime, violence, exploitation and neglect of children in every province in Indonesia, one ofLaw of the Republic of Indonesia No. 35 of 2014 confirms that children have the right to survival, growth and development and to receive protection from all acts of crime, violence, exploitation and neglect. Even though government regulations have been enacted, there are still cases of crime, violence, exploitation and neglect of children in every province in Indonesia, one of which is the Province of West Kalimantan. Based on this description, it is necessary to design a Social Rehabilitation Center for Children so they would receive protection, education, develop creativity, and improve their social skills in the community. The design is intended for children aged 6-12 years because they require different handling. The design method uses the R. Whittaker method which consists of an introduction stage, definition stage, preparation stage, analysis stage, synthesis stage, and evaluation stage. Social Rehabilitation Center for Children in West Kalimantan consist several building masses, such as management and health masses, education and therapy masses, and dormitory masses using an Architectural Psychology approach to create a safe and comfortable environment for children's growth and development. The embodiment of the Architectural Psychology approach adjusts to space requirements both physical and psychosocial as well as visual aspects which include sensory stimuli, such as shape, color, scale, lighting, ventilation, view, vegetation, and noise.which is the Province of West Kalimantan. Children who experience acts of violence both physically, psychologically, sexually, and socially can bring up various forms of behavior such as permissive, depressive, aggressive, and destructive. Based on this description, it is necessary to design a Social Rehabilitation Center for Children so they would receive protection, education, develop creativity, and improve their social skills in the community. The services provided at Social Rehabilitation Center for Children are in the form of physical guidance, social guidance and psychosocial therapy, mental-spiritual guidance, and skills guidance. The design is intended for children aged 6-12 years because they require different handling. Social Rehabilitation Center for Children in West Kalimantan consist several building masses, such as management and health masses, education and therapy masses, and dormitory masses using an Architectural Psychology approach to create a safe and comfortable environment for children's growth and development. The embodiment of the Architectural Psychology approach adjusts to space requirements both physical and psychosocial as well as visual aspects which include sensory stimuli, such as shape, color, scale, lighting, ventilation, view, vegetation, and noise.